Trauma patterns and injury prevalence in early medieval Säben‐Sabiona, Italy. (31st May 2021) - Tumler, Daniela; Paladin, Alice; Zink, Albert R.
Abstract: In the Early Middle Ages (fifth to 11th centuries AD), central Europe was marked by geo‐political instabilities and important socio‐cultural changes that led to the admixture of different cultures named barbari by the Romans, whose demographic impact is still not fully understood. These events also involved the populations settled in modern day South Tyrol, a region in the north‐eastern Italian Alps. In this context, the early medieval site of Säben‐Sabiona (Eisack‐Isarco valley, Province of Bozen‐Bolzano) had a relevant political role, and particularly due to its geographical location and religious importance, it was a prestigious burial site for individuals of different cultural and social backgrounds. This study aims to gain novel insights into the possible effects of these instabilities on daily life and general health of the people buried in Säben‐Sabiona, based on a thorough analysis of accident and violence‐related trauma. A total number of 226 individuals underwent a detailed osteological analysis to establish the number of individuals affected by trauma and to reconstruct the distribution, timing and type of injury. Trauma was assessed through macroscopic and metric analyses. Both crude, injuries per individual, and true prevalence rates, trauma per bone, were calculated. Signs of trauma were found on 37/226 individuals, whereby males exhibited more trauma than females and subadults. Most injuries were identified as antemortem fractures on the appendicular skeleton or perimortem sharp force trauma that was predominantly found on the skull. Most individuals featured less than five trauma; however, seven individuals account for more than half of the observed lesions. The trauma investigation suggests that most of the injured experienced skeletal injuries associated with labour‐related accidents and only a few, all of which were males, displayed signs of contemplated violence. Hence, it appears that the lives of the studied individuals were largely non‐violent, yet, sporadic situations of hostility and interpersonal conflict were also common.